2019
DOI: 10.1007/s10886-018-01044-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Protein Amino Acids in Nectar on Bee Survival and Behavior

Abstract: Nectar mediates complex interactions between plants and animals. Recent research has focused on nectar secondary compounds that may play a role in regulating some of these interactions. These compounds may affect the behavior of nectar feeders by interacting with their neurobiology. Non-protein amino acids (NPAAs) can constitute a large portion of the amino acid content of floral nectar, but their ecological function has, to date, not been investigated. In this study, we tested the effects of diets with low an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 41 publications
(48 reference statements)
5
33
1
1
Order By: Relevance
“…We also demonstrated that bees did not exhibit innate feeding preference between a plain sucrose solution and an equal solution laced with NPAAs in a two-minute assay. In line with a previous study [36], our 10-day-long toxicological assays showed that nectar NPAAs affected neither food consumption nor bees' longevity. Taken together, these results strongly suggest that nectar NPAAs at concentrations within the natural range do not alter nectar palatability, at least for the pollinator Apis mellifera.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also demonstrated that bees did not exhibit innate feeding preference between a plain sucrose solution and an equal solution laced with NPAAs in a two-minute assay. In line with a previous study [36], our 10-day-long toxicological assays showed that nectar NPAAs affected neither food consumption nor bees' longevity. Taken together, these results strongly suggest that nectar NPAAs at concentrations within the natural range do not alter nectar palatability, at least for the pollinator Apis mellifera.…”
Section: Discussionsupporting
confidence: 92%
“…However, this possibility fits poorly with our results, given that both GABA and β -alanine improved rather than weakened the acquisition level of bees encountering these NPAAs in the reinforcement offered during training. Improved acquisition in appetitive learning also did not reflect a generalized enhancement of feeding because in this and other studies [36] caged bees did not consume more food enriched with NPAAs. Moreover, in one assay freely moving bees did not prefer NPAA-free sucrose solutions.…”
Section: Discussionmentioning
confidence: 43%
“…Therefore on the basis of environmental stimuli (presence of pollinators and/or herbivores), a plant can: (i) control the production of nectar, (ii) regulate the quantity of nectar among its flowers so as to induce pollinators to visit more than one flower and increase out‐crossing, and (iii) modulate the presence of nutrients and secondary metabolites in the nectar. Based on the above, an intriguing theory has developed about the ability of plants to ‘manipulate’ pollinator visits, mainly of insects (Nepi et al, 2018; Bogo et al, 2019). Indeed, to optimize the flow of pollen between individuals, plants exercise control over the nectar standing crop, generating very variable production of nectar.…”
Section: Flowers Nectar and Fertilizationmentioning
confidence: 99%
“…Based on the fact that phenylalanine and GABA are known to elicit a strong phagostimulatory response in bees, the presence of these floral nectar-specific amino acids may function to attract this pollinator (Hendriksma et al, 2014; Nepi, 2014; Petanidou et al, 2006). GABA may also confer health benefits for bees as GABA-enriched artificial nectar has been shown to increase the locomotion and survival time of bees (Bogo et al, 2019). Leucine and tryptophan may also provide a desirable flavor due to stimulation of sugar chemosensory cells (Shiraishi and Kuwabara, 1970).…”
Section: Discussionmentioning
confidence: 99%